Virulence potential of multidrug-resistant Acinetobacter baumannii isolates from COVID-19 patients on mechanical ventilation: The first report from Serbia - Novović, Katarina; Kuzmanović Nedeljković, Snežana; Poledica, Mirjana; Nikolić, Gordana; Grujić, Bojana; Jovčić, Branko; Kojić, Milan; Filipić, Brankica (Frontiers in Microbiology, 2023)
Since the WHO declared the COVID-19 pandemic in March 2020, the disease has spread rapidly leading to overload of the health system and many of the patients infected with SARS-CoV-2 needed to be admitted to the intensive care unit (ICU). Around 10% of patients with the severe manifestation of COVID-19 need noninvasive or invasive mechanical ventilation, which represent a risk factor for Acinetobacter baumannii superinfection. The 64 A. baumannii isolates were recovered from COVID-19 patients admitted to ICU at General Hospital “Dr Laza K. Lazarević” Šabac, Serbia, during the period from December 2020 to February 2021. All patients required mechanical ventilation and mortality rate was 100%. The goal of this study was to evaluate antibiotic resistance profiles and virulence potential of A. baumannii isolates recovered from patients with severe form of COVID-19 who had a need for mechanical ventilation. All tested A. baumannii isolates (n = 64) were sensitive to colistin, while resistant to meropenem, imipenem, gentamicin, tobramycin, and levofloxacin according to the broth microdilution method and MDR phenotype was confirmed. In all tested isolates, representatives of international clone 2 (IC2) classified by multiplex PCR for clonal lineage identification, blaAmpC, blaOXA-51, and blaOXA-23 genes were present, as well as ISAba1 insertion sequence upstream of blaOXA-23. Clonal distribution of one dominant strain was found, but individual strains showed phenotypic differences in the level of antibiotic resistance, biofilm formation, and binding to mucin and motility. According to PFGE, four isolates were sequenced and antibiotic resistance genes as well as virulence factors genes were analyzed in these genomes. The results of this study represent the first report on virulence potential of MDR A. baumannii from hospital in Serbia.